Diversity and activity of group 5/1h high-affinity H2 oxidizing bacteria is non-responsive to pH - Lijun Hou; Philippe Constant; Joann K. Whalen (Soil Biology and Biochemistry, 2026)

Ecological traits of high-affinity hydrogen-oxidizing soil bacteria involved in the hydrogen cycle - Lijun Hou; Joann K. Whalen; Philippe Constant (Soil Biology and Biochemistry, 2025)

Corrigendum to “Spatial heterogeneity of high-affinity H2 oxidation activity in agricultural soil profile” [Soil Biol. Biochem. 202 (2025) 109703] - Lijun Hou; Philippe Constant; Joann K. Whalen (Soil Biology and Biochemistry, 2025)

Spatial heterogeneity of high-affinity H2 oxidation activity in agricultural soil profile - Lijun Hou; Philippe Constant; Joann K. Whalen (Soil Biology and Biochemistry, 2025)

An approach to assess hazards in the vicinity of mountain and volcanic areas - Andre Michel Pouth Nkoma; Jorelle Larissa Meli’i; Marthe Mbond Ariane Gweth; Blaise Pascal Gounou Pokam; Michel Constant Njock; William Assatse Teikeu; Ibrahim Mbouombouo Ngapouth; Yvonne Poufone Koffi; Richie Kevin Wouako Wouako; Philippe Njandjock Nouck (Landslides, 2025)

A rhizosphere effect promotes the persistence of gas oxidization activity in soil - Anne de la Porte; Audrey-Anne Durand; Joann Whalen; Étienne Yergeau; Philippe Constant (Soil Biology and Biochemistry, 2024)

How tree traits modulate tree methane fluxes: A review - Marie-Ange Moisan; Geneviève Lajoie; Philippe Constant; Christine Martineau; Vincent Maire (Science of The Total Environment, 2024)

Iron and Nickel Supplementation Exerts a Significant Positive Effect on the Hydrogen and Methane Production from Organic Solid Waste in a Two-Stage Digestion - Karina J. Salazar-Batres; Audrey-Anne Durand; Philippe Constant; Iván Moreno-Andrade (BioEnergy Research, 2023)
Two-stage anaerobic digestion and trace metals (TM) supplementation are promising techniques to improve biogas production. Fe 2+ and Ni 2+ can improve process stability since they are part of the cofactors of enzymes and microorganisms’ growth. This work attempted to evaluate the effect of Fe 2+ and Ni 2+ addition on H 2 -rich biogas production from organic solid waste and the CH 4 -rich biogas production from the acidogenic effluents (AEs) enriched with TM. The TM concentrations that enhanced the hydrogen yield in the batch were 0.25 mg/L of Ni 2+ and 334 mg/L of Fe 2+ . These concentrations were evaluated in a two-stage system. The substrate for the batch tests and fermentative reactor (first stage) was OSW. The AE generated in the first stage was the substrate to produce CH 4 -rich biogas in the second stage. In the first stage, the productivity achieved was 1823 ± 160 mL H 2 /L/day. However, TM supplementation decreased productivity by 65% since the VS removal increased. Megasphaera genus predominated in the first stage. Regarding the methanogenic reactor, the undiluted AE without TM caused the fast decay of the process. Nevertheless, the reactor operated stably after using AE enriched with TM as a substrate, and CH 4 yields increased by 42%. The highest productivity achieved in the second stage was 1278 ± 42 mL CH 4 /L/day, operating with an organic loading rate of 2.8 gVS/L/day. The genera Proteiniphilum , Thermovirga , DMER64 , Anaerovorax , and Syntrophomonas predominated in the second stage. In conclusion, AE enriched with TM can be used to recover the stability of anaerobic digesters, increasing methane production.

Pseudomonas aeruginosa isolates defective in function of the LasR quorum sensing regulator are frequent in diverse environmental niches - Marie‐Christine Groleau; Hélène Taillefer; Antony T. Vincent; Philippe Constant; Eric Déziel (Environmental Microbiology, 2022)
Summary The saprophyte Pseudomonas aeruginosa is a versatile opportunistic pathogen causing infections in immunocompromised individuals. To facilitate its adaptation to a large variety of niches, this bacterium exploits population density‐dependent gene regulation systems called quorum sensing (QS). In P. aeruginosa , three distinct but interrelated QS systems ( las , rhl and pqs ) regulate the production of many survival and virulence functions. In prototypical strains, the las system, through its transcriptional regulator LasR, is important for the full activation of the rhl and pqs systems. Still, LasR‐deficient isolates have been reported, mostly sampled from the lungs of people with cystic fibrosis, where they are considered selected by the chronic infection environment. In this study, we show that a defect in LasR activity appears to be an actually widespread mechanism of adaptation in this bacterium. Indeed, we found abundant LasR ‐ defective isolates sampled from hydrocarbon‐contaminated soils, hospital sink drains and meat/fish market environments, using an approach based on phenotypic profiling, supported by gene sequencing. Interestingly, several LasR‐defective isolates maintain an active rhl system or are deficient in pqs system signalling. The high prevalence of a LasR‐defective phenotype among environmental P. aeruginosa isolates questions the role of QS in niche adaptation.

Detection and isolation of plant‐associated bacteria scavenging atmospheric molecular hydrogen - Manabu Kanno; Philippe Constant; Hideyuki Tamaki; Yoichi Kamagata (Environmental Microbiology, 2016)
Summary High‐affinity hydrogen ( H 2 )‐oxidizing bacteria possessing group 5 [ NiFe ]‐hydrogenase genes are important contributors to atmospheric H 2 uptake in soil environments. Although previous studies reported the occurrence of a significant H 2 uptake activity in vegetation, there has been no report on the identification and diversity of the responsible microorganisms. Here, we show the existence of plant‐associated bacteria with the ability to consume atmospheric H 2 that may be a potential energy source required for their persistence in plants. Detection of the gene hhyL – encoding the large subunit of group 5 [ NiFe ]‐hydrogenase – in plant tissues showed that plant‐associated high‐affinity H 2 ‐oxidizing bacteria are widely distributed in herbaceous plants. Among a collection of 145 endophytic isolates, seven S treptomyces strains were shown to possess hhyL gene and exhibit high‐ or intermediate‐affinity H 2 uptake activity. Inoculation of A rabidopsis thaliana (thale cress) and O ryza sativa (rice) seedlings with selected isolates resulted in an internalization of the bacteria in plant tissues. H 2 uptake activity per bacterial cells was comparable between plant and soil, demonstrating that both environments are favourable for the H 2 uptake activity of streptomycetes. This study first demonstrated the occurrence of plant‐associated high‐affinity H 2 ‐oxidizing bacteria and proposed their potential contribution as atmospheric H 2 sink.

Toxicity survey of Canadian Arctic marine sediments - João Canário; Laurier Poissant; Martin Pilote; Christian Blaise; Philippe Constant; Jean-François Férard; François Gagné (Journal of Soils and Sediments, 2014)

Streptomycetes contributing to atmospheric molecular hydrogen soil uptake are widespread and encode a putative high‐affinity [NiFe]‐hydrogenase - Philippe Constant; Soumitra Paul Chowdhury; Jennifer Pratscher; Ralf Conrad (Environmental Microbiology, 2010)
Summary Uptake of molecular hydrogen (H 2 ) by soil is a biological reaction responsible for ∼80% of the global loss of atmospheric H 2 . Indirect evidence obtained over the last decades suggests that free soil hydrogenases with an unusually high affinity for H 2 are carrying out the reaction. This assumption has recently been challenged by the isolation of Streptomyces sp. PCB7, displaying the high‐affinity H 2 uptake activity previously attributed to free soil enzymes. While this finding suggests that actinobacteria could be responsible for atmospheric H 2 soil uptake, the ecological importance of H 2 ‐oxidizing streptomycetes remains to be investigated. Here, we show that high‐affinity H 2 uptake activity is widespread among the streptomycetes. Among 14 streptomycetes strains isolated from temperate forest and agricultural soils, six exhibited a high‐affinity H 2 uptake activity. The gene encoding the large subunit of a putative high‐affinity [NiFe]‐hydrogenase ( hydB ‐like gene sequence) was detected exclusively in the isolates exhibiting high‐affinity H 2 uptake. Catalysed reporter deposition‐fluorescence in situ hybridization (CARD‐FISH) experiments targeting hydB ‐like gene transcripts and H 2 uptake assays performed with strain PCB7 suggested that streptomycetes spores catalysed the H 2 uptake activity. Expression of the activity in term of biomass revealed that 10 6 –10 7 H 2 ‐oxidizing bacteria per gram of soil should be sufficient to explain in situ H 2 uptake by soil. We propose that specialized H 2 ‐oxidizing actinobacteria are responsible for the most important sink term in the atmospheric H 2 budget.